STRATEGI MANAJEMEN SEKOLAH DALAM PENGEMBANGAN INFORMASI DAPODIK DI INTERNET - Annida Annida; Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Through an integrated dapodik management information system strategy (integrated) can provide more accurate and quality information to support the development of operations, management, and decision- making functions within an organization. The school's strategy in analyzing the internal and external environment, the chosen strategy in improving the quality of basic education is through a curriculum program strategy, a program to improve the quality of educators and education staff. Therefore, we need a qualified operator and educator who can create conditions so that all components are interrelated and can work well together to achieve school goals.